TINGKAT KESUKAAN MI BASAH DENGAN PENAMBAHAN TEPUNG IKAN GABUS - Sari, Elviana Dian Mustika; Pratama, Rusky Intan; Andhikawati, Aulia; Rostini, Iis (Jurnal Perikanan Unram, 2025)
Snakehead (Channa striata) is a high-protein fish that is less preferred for direct consumption. Through food diversification, snakehead fish meat can be processed into fish flour and incorporated into various food products, including wet noodles. This study aims to determine the optimal concentration of snakehead fish flour to produce wet noodles with the highest panelist preference. The method used was a laboratory experimental method, involving the preparation of wet noodles with snakehead flour at four different concentrations (0%, 5%, 10%, and 15%) and an evaluation by 25 semi-trained panelists to determine their preferences. The parameters observed included fishmeal yield, panelist preferences, and the chemical composition of wet noodles. The 10% snakehead flour treatment was the most preferred, with the highest alternative value of 8.05, and average scores for appearance (8.12), aroma (5.80), texture (6.68), and taste (7.72). The chemical composition of the 10% treatment included 10% protein content, 33.94% water content, 7.54% ash content, 3,85% fat content, and 44,67% carbohydrate content.